2014
DOI: 10.1063/1.4894171
|View full text |Cite
|
Sign up to set email alerts
|

Loparite-(Ce), a natural ferroelectric with the perovskite-type structure

Abstract: We report on the results of studies of dielectric properties of loparite-(Ce), a naturally occurring member of the perovskite-type family of materials, in the temperature range of 80–400 K. A strong frequency dispersion attributable to disorder and a dielectric anomaly have been observed in the vicinity of T = 157 K. The behavior of the inverse dielectric permittivity 1/ε′(T) has been found to be well described by the Curie–Weiss law with parameters C = 2.2 × 105 K−1 and Tm = 157 K. Studies of a dielectric hys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Indeed, anomalies in the dielectric permittivity of loparite‐(Ce) have been observed . The analysis of the dielectric response reported in showed that the temperature behavior of the inverse dielectric permittivity in the vicinity of 157 K obeys the Curie–Weiss law with the value of the Curie constant typical of ferroelectric phase transitions in perovskites. Hysteresis loops and behavior of the temperature dependence of spontaneous polarization given in the paper indicate that a ferroelectric state arises in loparite‐(Ce)–Се at Т < 157 K. The temperature behavior of conductivity and dielectric permittivity in the vicinity of 220 K confirm our hypothesis that there is a lattice instability near 220 K .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, anomalies in the dielectric permittivity of loparite‐(Ce) have been observed . The analysis of the dielectric response reported in showed that the temperature behavior of the inverse dielectric permittivity in the vicinity of 157 K obeys the Curie–Weiss law with the value of the Curie constant typical of ferroelectric phase transitions in perovskites. Hysteresis loops and behavior of the temperature dependence of spontaneous polarization given in the paper indicate that a ferroelectric state arises in loparite‐(Ce)–Се at Т < 157 K. The temperature behavior of conductivity and dielectric permittivity in the vicinity of 220 K confirm our hypothesis that there is a lattice instability near 220 K .…”
Section: Resultsmentioning
confidence: 97%
“…Significant changes in the phonon frequencies should also be reflected in the temperature dependence of the dielectric response through the Lyddane–Sach–Teller relation . Indeed, anomalies in the dielectric permittivity of loparite‐(Ce) have been observed . The analysis of the dielectric response reported in showed that the temperature behavior of the inverse dielectric permittivity in the vicinity of 157 K obeys the Curie–Weiss law with the value of the Curie constant typical of ferroelectric phase transitions in perovskites.…”
Section: Resultsmentioning
confidence: 97%